(untitled) (International journal of artificial intelligence, 2024)
Public diplomacy has become an increasingly vital tool for multilateral organizations as they navigate complex global landscapes. Institutions like NATO, the European Union (EU), and the Association of Southeast Asian Nations (ASEAN) employ public diplomacy to enhance their global image, foster cooperation, and address pressing international issues. This article examines how these organizations engage in public diplomacy, the strategies they employ, and the challenges they face.